2005
DOI: 10.1097/01.jom.0000150208.20117.34
|View full text |Cite
|
Sign up to set email alerts
|

Performance Decrements Resulting From Illness in the Workplace: The Effect of Headaches

Abstract: The three groups were similar in a variety of demographic factors, and mean subject-specific measures of speed, output, and productivity. In a multivariate model using general estimating equations, only episode severity (not type of headache or person-specific diagnosis) was found to be associated with a significant decrement in speed or productivity. The self-reported decrement in speed (approximately 20%) was much greater than the actual measured effect on productivity (approximately 8%). Intensive daily dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
18
2
1
Order By: Relevance
“…The third study collected data from respondents with headaches, and participants were diagnosed as having migraine or other types of headache by a neurologist when the study was complete. 33 Four of the 9 studies on burden of migraine reported the mean cost of lost workplace productivity. 5,17,20,35 Stang and Osterhaus 5 calculated a national estimate of the cost and number of days of restricted activity due to migraine.…”
Section: Burden Of Migraine On Us Worker Productivitymentioning
confidence: 99%
See 3 more Smart Citations
“…The third study collected data from respondents with headaches, and participants were diagnosed as having migraine or other types of headache by a neurologist when the study was complete. 33 Four of the 9 studies on burden of migraine reported the mean cost of lost workplace productivity. 5,17,20,35 Stang and Osterhaus 5 calculated a national estimate of the cost and number of days of restricted activity due to migraine.…”
Section: Burden Of Migraine On Us Worker Productivitymentioning
confidence: 99%
“…Other studies estimated the mean number of hours of work lost per attack (8.2 hours), 27 the mean number of hours lost per year (88 hours), 34 the mean number of days of work lost per year (4.4 days), 32 and the median number of days of work lost per year (4 days). 30 Pransky et al 33 administered daily surveys with a telephone interactive voice response system and found that 14.6% of workdays for migraineurs were affected by a headache.…”
Section: Burden Of Migraine On Us Worker Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Methods to measure reduced productivity have been developed (5,7,19) for disorders such as depression, rheumatoid arthritis, migraine headaches, sleep disorders, and diabetes (20)(21)(22)(23)(24) or health risks (8,25). Some studies with a cross-sectional study design have reported possible correlations between musculoskeletal symptoms and productivity loss (4,8,(15)(16)(17)26).…”
mentioning
confidence: 99%